Pengaruh pengalaman audit dan pengetahuan audit terhadap keahlian dalam bidang auditing pada badan pemeriksa keuangan (bpk) ri perwakilan provinsi riau - Intan Dewi Rahayu Ningsih; Rita Anugerah; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to examine the effect of auditor’s audit experience and auditor’s audit knowledge on auditor’s expertise of BPK RI delegation in Riau Province. The data collecting method used in this research is survey method by means of questionnaire instrument directly delivered to BPK RI delegation in Riau province. A total of 36 respondents (90%) collected and used in the analysis. Methods of analysis used in this study is the technique of multiple regression analysis version 17.0. Result of the study showed that the variables auditor’s audit experience and auditor’s audit knowledge effect on the auditor expertise. The magnitude of the effect caused by Adjusted R2 by two variables together 59.5% of the dependent variable, while the remaining 40.5% is influenced by other variables not examined in this study.Keyword : auditor expertise, audit’s experience, and audit’s knowledge.